Wheat Quality Requirements for Char Siew Bao Made from Australian Soft Wheat - Limley, H.; Crosbie, G.; Lim, K.; Williams, H.; Diepeveen, D.; Solah, Vicky (A A C C International, 2013)
Australia exports 75% of the wheat produced annually, and the Asian region is an important export market for Australian wheat. These markets require suitable quality grain for use in wheat-based products, so the understanding of wheat end products from an Asian consumer point of view is important. The major wheat quality requirements for char siew bao, a Chinese Guangdong-style steamed bun, were determined. The research 1) developed laboratory methods for the production and assessment of char siew bao using a scoring system; 2) optimized the new methods and compared the new methods with a traditional method; and 3) used the new validated methods in an investigation of the role of soft wheat quality on char siew bao. A sponge-and-dough method with 1 hr fermentation time was developed to establish a simplified laboratory method for char siew bao production. The screening experiments and response surface methodology experiments showed that water addition, sugar, and sponge mixing time were responsible for 69% of the variation in total score. Dough strength was the most important parameter affecting char siew bao quality, followed by flour swelling volume, protein content, and dough extensibility. Both protein and starch quality were important determinants of char siew bao quality.